Clinical outcomes of EGFR kinase domain duplication to targeted therapies in NSCLC. Issue 11 (16th December 2018) - Wang, Jinguang; Li, Xingya; Xue, Xingyang; Ou, Qiuxiang; Wu, Xue; Liang, Ying; Wang, Xiaonan; You, Ming; Shao, Yang W.; Zhang, Zhihong; Zhang, Shucai
Abstract : Kinase domain duplications of the epidermal growth factor receptor (EGFR‐KDD) have been identified and implicated to be oncogenic in nonsmall cell lung cancers (NSCLCs). However, its prevalence and clinical contributions in lung cancer are largely unknown. Here, we conducted a multicenter record review of 10, 759 NSCLC patients who underwent genetic testing using next‐generation sequencing (NGS) targeting EGFR exons and the introns involved in EGFR‐KDD rearrangements. EGFR‐KDDs were identified in a total of 13 patients, which is approximately 0.12% of the total population reviewed, and also consisted of 0.24% (13/5394) of EGFR mutation‐positive patients. A total of 85% of patients (11/13) were identified with the canonical EGFR‐KDD duplication of exons 18–25, while the remaining two cases harbored duplications of EGFR exons 14–26 and exons 17–25, which have not been previously described. Importantly, none of the 13 patients had other coexisting driver mutations, highlighting the potential oncogenic role of this type of alteration. Three out of five patients who had exon 18–25 duplications showed partial antitumor responses to targeted therapies, while the other two patients demonstrated no clinical improvement. Furthermore, our data suggested that the EGFR T790 M mutation and EGFR amplification may represent the major resistance mechanisms against targeted therapies in tumors bearing EGFR‐KDD. In summary, our findings provide valuable insight into the prevalence of EGFR‐KDDs in NSCLCs and their clinical outcomes to targeted therapies. Abstract : What's new? A rare class of mutation could provide a therapeutic target for lung cancer. Many NSCLCs arise with mutations in the EGFR tyrosine kinase domain, and treatment with EGFR tyrosine kinase inhibitors often boosts survival in these patients. Usually, these are deletions or point mutations, but sometimes the mutation is a kinase domain duplication (KDD). These authors investigated how frequently EGFR‐KDDs occur, and whether tyrosine kinase inhibitors work against them. By reviewing records from thousands of NSCLC patients, they discovered 13 EGFR‐KDDs. Tyrosine kinase inhibitors did suppress some of the tumors, although resistance arose in the event of additional EGFR mutations.